Effect of lifestyle and socioeconomic status in type I diabetes in children - Hassan, Khaled M.; Suwaydi, Abdulbaqi A.; Alshikh, Abdulaziz A.; Alkhairi, Afnan M.; Nassir, Asmaa Y.; Al-Ahmari, Hamoud O.; Alamri, Mohammed A.; Alghammas, Saleh I.; Albalawi, Abdulelah S.; Samman, Bayan R.; Ananarah, Ibrahim M.; Aldarwish, Ahlam A.; et al. (International Journal Of Community Medicine And Public Health, 2020)
Background: This study describes the effect of life style and socioeconomic state in children diagnosed with type 1 diabetes mellitus. The study was conducted in different health centers in Mexico, to clarify and describe relationship between life style, socioeconomic state and occurrence of diabetes type I. Methods: The sample was 65 children with similar characteristics, they agreed to participate in the study, from July 2012 to September 2012. IMEVID was used to describe effect of lifestyle and socioeconomic state. Results: 29.23% has been applied to sustain a "good lifestyle", which corresponded to a "healthy" rating, but highest concentration were in an inappropriate lifestyle (70.77%), classified into two classifications 56.92% was "moderately healthy" and only 13.85% was "unhealthy" behavior. Significant correlation between the styles of life evaluated and considered dimensions, except with the emotional state was found. Relationship existed between the style of life evaluated and perceived by patients. Conclusions: Gradual clarification of the concept known as "lifestyle" has enabled the health sciences resize the notion of the state of "health and disease"; results are consistent with other studies conducted in Mexico.